Анализ роста вегетативных органов Ocimum basilicum L. (Lamiaceae Lindl.) в условиях Донбасса - Кустова, О.К. (Промышленная ботаника, 2003)
The regression relations of the growth of Ocimum basilicum L. varieties vegetative organs under the conditions of Donbass: duration, rate of the growth of leave blades and the main shoot were fixed and mathematically proved. Based on the data obtained, an additional diagnostic feature of the intraspecific classification – length of the leaf – was discovered. Intensity of accumulation of the standing crop in plants of the samples with good prospects was traced in dynamics on the background of the daily average air temperature under the conditions of experiment.